The flexibility of macrocyclic rings and the different spatial conformations of metallated and non-metallated macrocyclic compounds (Research, Society and Development, 2023)
The chemistry of macrocyclic compounds is one of the areas with the greatest implications in several multi- and interdisciplinary areas, such as biological chemistry, materials chemistry, the chemistry of metal complexes and the so-called “supramolecular chemistry”. In fact, both in complexed and non-complexed form, such compounds are highly relevant. When it comes to so-called macrocyclic complexes, the well-known “macrocyclic effect” is the way in which the extraordinary kinetic and thermodynamic stabilities of such compounds are mentioned. Furthermore, macrocyclic coordination compounds are often formed, together with the concomitant formation of the macrocycle itself, that is, the precursors of macrocycle formation are united through the inducing-organizing action of the metal cation itself and/or coordination center. (which is known as “template effect”). There are several types of relevant macrocycles, such as, for example, tetraazamacrocycles, known for various importance, from the presence in prosthetic groups of relevant metalloproteins, such as porphyrins, among other macrocycles, to applications as photosensitizers in photodynamic therapy (PDT) and biosensors. The present study presents an introduction to the respective topic, covering an initial discussion on the different spatial conformations that free macrocycles or in their metallated forms can present and their implications. This work of literature revision aims to contribute to the discussion focused on such compounds, considering that their distinct spatial conformations are decisive for the respective structure-function relations, which has not always been considered in the different lines of research that pervade the chemistry of macrocycles.